AEROSOL BACKGROUND LAPISAN STRATOSFER DI ATAS BANDUNG (6˚54'LS 107˚35'BT) BERDASARKAN PENELITIAN TAHUN 1997-2000 MENGGUNAKAN RAMAN LIDAR - Saipul Hamdi; Sri Kaloka; Iis Sofiati; Afif Bidiyono (Lembaga Penerbangan dan Antariksa Nasional, 2005)
Aerosol background observation over Bandung (6˚54'S 107˚35'E) using LIDAR has being done since 1997 as a part of global LIDAR network coordinated by Japan. The 5 years dta shows that the Integrated Backscattering Coefficient at altitude 18-35 km is very small, in the order of 10-6 sr-1. It is 1/100 times compared to IBC over Japan 4 years after Pinatubo eruption. The altitude of IBC weight is relatively stable, in the range of 20-25 km.